Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1111/gtc.12389
|View full text |Cite|
|
Sign up to set email alerts
|

TargetingID2expression triggers a more differentiated phenotype and reduces aggressiveness in human salivary gland cancer cells

Abstract: Inhibitors of DNA-binding (ID) proteins are negative regulators of basic helix-loop-helix transcription factors and generally stimulate cell proliferation and inhibit differentiation. We previously determined that ID1 was highly expressed in aggressive salivary gland cancer (SGC) cells in culture. Here, we show that ID2 is also expressed in aggressive SGC cells. ID2 knockdown triggers important changes in cell behavior, that is, it significantly reduces the expression of Ncadherin, vimentin and Snail, induces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Id proteins are negative regulators of basic helix‐loop‐helix transcription factors and generally stimulate cell proliferation and inhibit differentiation . A couple of mechanisms underlying growth‐regulatory function of Id proteins have been explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Id proteins are negative regulators of basic helix‐loop‐helix transcription factors and generally stimulate cell proliferation and inhibit differentiation . A couple of mechanisms underlying growth‐regulatory function of Id proteins have been explored.…”
Section: Discussionmentioning
confidence: 99%
“…Activated Smads bind to Smad-binding elements (SBE) on Id promoter resulting in transcription of Id proteins 29. Id proteins are negative regulators of basic helix-loop-helix transcription factors and generally stimulate cell proliferation and inhibit differentiation 30,31. A couple of mechanisms underlying growth-regulatory function of Id proteins have been explored.…”
mentioning
confidence: 99%
“…ID2 was significantly overexpressed in all CDDP-resistant TGCT cell lines. In other cancers, the ID2 protein promotes early-stage progression [83] and survival during metabolic stress [84], and its defect leads to a more differentiated less aggressive phenotype [85]. We found no significant changes in ISG20 expression, although ISG20 is a protein whose forced expression leads to significant promotion of metastasis and angiogenesis in hepatocellular carcinoma [86].…”
Section: Discussionmentioning
confidence: 53%
“…When inflammation and cell proliferation and differentiation appeared, it was induced by cytokines, growth factors and tumor promoters, and its expression could be rapidly increased by 8-10 times. COX-2 is a rate-limiting enzyme of prostaglandin production, which is widely considered as one of the important inducible enzymes in inflammatory process [17] . Recent studies have found that the biological function of COX-2 can enhance the angiogenesis of subunit fibroblast growth factor and VEGF by stimulating the mitosis of human endothelial cells [18] .…”
Section: Resultsmentioning
confidence: 99%